Analysis of suction distribution response to rainfall event and tree canopy - Mohd Fakhrurrazi, Ishak; Nazri, Ali; Azman, Kassim (Penerbit Universiti Teknologi Malaysia, 2016)
This study provides an exploration of matric suction influenced by tree canopy interception on a single rainfall event. A field monitoring was carried out to measure matric suction at slope with two conditions; at toe of slope without tree and with a tree at toe of slope on a tropical residual soil. The variation in matric suction values and matric suction profiles response to the rainfall events on slope with and without a tree at toe were analysed to reveal the effect of the tree canopy. At initial condition, the matric suction was significantly higher at vicinity of tree compared to that of area without tree at toe of slope. However, a typical short and intense tropical rainfall has caused the matric suction to drop dramatically to a minimum value on slope without tree. This condition did not occur on slope with tree. Although, both slopes (with and without tree at toe) received the same amount of precipitation rainfall but the different responses in matric suction valueswere clearly shown at slope with tree at the slope toe. The short and intense rainfalls appeared to be the dominant factor to the suction variation at slope without tree, but not at slope with the tree. The tree canopy can be a factor to influence the suction variation at slope with tree as canopy interception reduced the amount of precipitation to the ground/sloping surface